EFFECTIVENESS OF ECONOMIC DIAGNOSIS OF THE QUALITY OF HIGHER EDUCATION - Jo‘rayev Soxibjon Nodirbek o‘g‘li (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2023)
The article reveals the importance of economic diagnostics in researching a higher education institution. The role of economic diagnostics in ensuring the efficiency of the higher education institution and the importance of diagnostic models are highlighted. A scientific proposal and practical recommendations are given to diagnose the economic and financial situation of the higher educational institution or the trends of changes in it.